Фібули V - першої половини VIII ст. з Полтавщини (знахідки від початку 2000-х років) - Володарець-Урбанович, Я.В. (Археологія, 2015)
Публікуються знахідки фібул епохи раннього середньовіччя з Полтавщини, виявлені з початку 2000-х рр. Визначено їх типологічну належність і хронологію побутування, наведено аналогії. Фибулы эпохи раннего средневековья юга Восточной Европы всегда были в центре внимания исследователей. Тем и обусловлен особый интерес к новым находкам. В частности, на территории Полтавской обл. выявлены фибулы у сел Малый Вязовок, Павловка, Шедиево (2 екз.), Засулье-Мгар (3 екз.), Батьки и Ковали (2 екз.) (рис. 1; 2). Именно их анализу и посвящена данная статья.
Находка сложной антропоморфной фибулы из Малого Вязовка принадлежит к Приходнюк/тип vI—Д или Родинкова/тип ІІ. 2. Аналогии происходят из Пастырского городища, а также ряда пунктов из Среднего Подне- провья и Днепровского Левобережья.
Находка простой антропоморфной фибулы из Павловки принадлежит к Родинкова/тип І.2.А. Полных анало- гий данному изделию найти не удалось. Наиболее близкие по форме фибулы выявлены на пеньковских памят- никах Среднего Поднепровья и Надпорожья, в кладах первой группы по О.А. Щегловой и из могильников типа нижнего слоя Суук-Су в Крыму.
Одна из находок из Шедиевого принадлежит к фибулам с каймой из птичьих голов, подтипа семиголовых, се- рии Б и варианта Майорки по В.Е. Родинковой. Аналогичные изделия происходят из балки Майорка, Козеевско- Новоодесского клада и Кузьминского могильника. Определить принадлежность второй пальчатой фибулы невоз- можно из-за ее фрагментарности.
Одна из трех фибул из Засулья-Мгара принадлежит к простым антропозооморфным Родинкова/тип І.2. Ана- логии происходят из балки Яцевой, Градижска и Великой Кручи. Вторая находка принадлежит к широкопла- стинчатым Гавритухин/тип 2б. Аналогии выявлены на пеньковских и колочинских памятниках и кладах первой хронологической группы по О.А. Щегловой. Третья фибула принадлежит к группе керченских пальчатых фи- бул — тип Керчь, подгруппа А, вид Iv. Аналогии происходят из Боспорского могильника в Крыму, Игрени, Бере- зовки и Кидановки в Среднем Поднепровье, на городище Спас-Перекша в Верхнем Поднепровье.
Малая пальчатая фибула из Батькив принадлежит к Гавритухин/тип Пергамон — Бухарест — оз. Тей, подтип неорнаментованных, серия А. Определить вариант (Селиште или Черкеский Бишкин) невозможно из-за фраг- ментированости изделия, так как определяющим элементом является форма ножки.
Одна из фибул из Ковалей относится к переходному типу от двухпластинчастых к пальчатым. Аналогии из- вестны на поселении Теремцы, жилище 14, на могильнике Веймар, погребение 1 (Германия), в Крыму (Керчь и Херсонес) и в Центральном Предкавказье и Северо-Восточном Кавказе (Чегем та Бачил-аул).
Вторая находка принадлежит к двухпластинчастым фибулам. Аналогичные изделия выявлены на поселении пеньковской культуры Новоселица и в составе клада первой хронологической группы Суджа-Замостья.
Роль фибул в костюме важна. Но для славянских древностей все реконструкции убора остаются на уровне гипотетических. Тем не менее, новые находки расширяют наши представления о типологическом разнообразии, эволюции и ареалах находок и помогают выявить направления торговых и экономических связей, путей мигра- ций, выделить отдельные культурно-исторические области. Кроме того, они важны как изделия древнего искус- ства, отображающие этапы духовного развития населения и особенности его верований. Хронология большин- ства изделий, рассмотренных в работе, укладывается в период vI — начала vIII вв. — от начала формирования убора первой хронологической группы кладов до выпадения кладов второй группы. Только находки из Ковалей бытуют в v — начале vI в. Fibulae of the Early Mediaeval period from the south of Eastern Europe were always in the centre of the scholars’ attention. this fact caused a special interest in the new finds. For instance, fibulae were found on the territory of Poltava oblast near the villages of Malyi viazovok, Pavlivka, Shediyeve (2 items), zasullia-Mhar (3 items), Batky, and kovali (2 items). these are analyzed in this article.
a finding of a complicated anthropomorphous fibula at Malyi viazovok belongs to Prykhodniuk/type vI—Д or Rodnikova/ type II.2. Its analogies come from Pastyrske hill-fort, as well as from a series of sites in the Dnipro River middle and left bank regions.
a finding of a simple anthropomorphous fibula from Pavlivka belongs to Rodnikova/type I.2.a. this item’s direct analogies are not found. the closest fibulae by their form were found at Penkivka culture sites of the Dnipro River middle region and Nadporizzhia, in the hoards of the first group, according to o.a. Shcheglova, and at the burial grounds of the type of the lower layer at Suuk-Su in the Crimea.
one of the finds from Shediyeve belongs to the fibulae with a border of birds’ heads, subtype of seven-headed, series Б and a variant Mayorka, according to v.ye. Rodnikova. analogous items come from Mayorka gully, koziyivka-Nova odesa hoard, and from kuzmynkskyi burial ground. It is impossible to determine the type of the other radiate-headed fibula because it’s too fragmentary.
one of three fibulae from zasullia-Mhar belongs to simple anthropo- and zoomorphous products, Rodnikova/type I.2. Its analogies come from yatseva gully, hradyzk and velyka krucha. the second find belongs to wide-plated, havrytukhin/ type 2б. Its analogies were found at Penkivka and kolochyn cultures sites and in hoards of the first chronological group, by o.a. Shcheglova. the third fibula belongs to the group of kerch radiate-headed fibulae: type kerch, subgroup a, type Iv. Its analogies come from the Bosporan burial ground in the Crimea, Ihren, Berezivka, and kydanivka in the Dnipro River middle region, and from Spas-Pereksha hill-fort in the Dnipro River upper region.
a small radiate-headed fibula from Batky belongs to havrytukhin/type Pergamum – Bucharest – tay lake, subtype not ornamented, series a. It is impossible to determine its variant, Selişte or Cherkessian Bishkin, because the item is fragmentary, while the determinative element is a form of a leg.
one of fibulae from kovali belongs to the transitional type from two-plated to radiate-headed fibulae. Its analogies are known at teremtsi settlement, dwelling 14, at Weimar burial ground, burial 1 (Germany), in the Crimea (kerch and Chersonesos), and in the North and North-Eastern Caucasus (Chegem and Bachil-aul).
the second find belongs to two-plated fibulae. analogous items were found at Novoselytsia settlement of Penkivka culture in the hoard of the first chronological group Sudzha-zamostia.
Fibulae play an important role in the costume. however, all the reconstructions of the clothes for Slavonic antiquities remain at the hypothetical level because of lack of information concerning their localization in the burials. Nevertheless, the new finds widen our idea on typological diversity, evolution, and the circuit of the findings and help to determine the ways of trading and economic relations, ways of migrations, and separate cultural and historical regions. Moreover, they are important as pieces of ancient art representing the stages of spiritual development of the population and the peculiarities of the religious beliefs. Chronology of most of the items discussed keep within the period from the 6th to the beginning of the 8th centuries: since the clothes of the first chronological group of the hoards started to develop, until the hoards of the second group appeared. only the finds from kovali were used in the 5th and in the beginning of the 6th centuries.